ANALISIS JENIS PONDASI GEDUNG MESJID AGUNG KOTA TANJUNG BALAI - Irwansyah Irwansyah; Sufrial Hendri (Universitas Quality, 2021)
Tanjungbalai City is one of the cities in North Sumatra Province with a population that continues to increase. Tanjungbalai City Government strives to provide services to the community by building a proper and adequate prayer facility in the city of Tanjungbalai. The Grand Mosque accommodates educational activities, a means of interaction, a good place of worship in Tanjungbalai City. Construction of a representative Grand Mosque which becomes the area's